ECONOMETRICAL EVIDENCE ON THE EFFECTS OF FOREIGN DIRECT INVESTMENT ON THE ECONOMY OF RECEIVING COUNTRIES: A METHODS-BASED REVIEW (Marketing Journal, 2025)
This article reviews global empirical studies on the impact of inward foreign direct investment (FDI) using key econometric methods. While many studies confirm that FDI positively affects growth, productivity and employment, the results vary significantly depending on the method used and country -specific conditions. The review underscores the importance of selecting appropriate econometric techniques tailored to data availability and policy objectives in countries like Uzbekistan.
Keywords: foreign direct investment; economic growth; econometric methods; panel data; causality; FDI absorptive capacity 68